Decision Support System Selection of Best Employee At PT. Intiberkah Sinar Sejahtera Using Simple Additive weighting Method - Feri Sahputra; Fricles Ariwisanto Sianturi (Information Technology and Science (ITScience), 2020)
The problem of PT. Sinar Sejahtera Intiberkah are still many employees of PT. Intiberkah Sinar Sejahtera especially the logistics employees who are critical to the company that should be worthy to obtain as the best employees but until now there has been no employees at the logistics become the best employee in the company of PT. Sinar Sejahtera Intiberkah tersebut.Oleh Therefore, in this study used a decision support system that can be used to help the PT. Intiberkah Sinar Sejahtera in determining the eligible employees in the selection of the best employees, there are four criteria taken in these elections is the first no ethical criteria, these criteria related to attitudes and ways of speaking with courtesy to superiors.